Trace elements and ingested plastic debris in wintering dovekies (Alle alle). Issue 1 (15th February 2015) - Fife, Danielle T.; Robertson, Gregory J.; Shutler, Dave; Braune, Birgit M.; Mallory, Mark L.
Highlights: First report on winter trace metal concentrations and ingested plastic in dovekies. They forage at lower trophic levels than dovekies from Svalbard, based on isotopes. Winter Hg and other trace elements generally low compared to other Arctic seabirds. Dovekies feeding at higher trophic levels had higher hepatic Hg. Plastic debris was found in nine of 65 (14%) gizzards examined. Abstract: We provide the first report on winter concentrations of 32 trace metals from dovekies ( Alle alle ), a small, Arctic seabird that has a seasonal shift in diet from small zooplankton in the breeding season to larger zooplankton and small fish in the non-breeding season. Concentrations of selected trace elements, as well as stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope concentrations for a sample of 25 dovekies, were similar between adult males and females, and there was evidence that dovekies feeding at higher trophic levels had higher hepatic Hg. We also found plastic debris in nine of 65 (14%) gizzards examined. Our study helps provide a more complete picture of the foraging ecology and contaminant profile of dovekies, an important species in Arctic marine food webs.